Substrate recognition by Escherichia coli MutY using substrate analogs. - Chepanoske, C L (1999)
The Escherichia coli adenine glycosylase MutY is involved in the repair of 7,8-dihydro-8-oxo-2"-deoxyguanosine (OG):A and G:A mispairs in DNA. Our approach toward understanding recognition and processing of DNA damage by MutY has been to use substrate analogs that retain the recognition properties of the substrate mispair but are resistant to the glycosylase activity of MutY. This approach provides stable MutY-DNA complexes that are amenable to structural and biochemical characterization. In this work, the interaction of MutY with the 2"-deoxyadenosine analogs 2"-deoxy-2"-fluoroadenosine (FA), 2"-deoxyaristeromycin (R) and 2"-deoxyformycin A (F) was investigated. MutY binds to duplexes containing the FA, R or F analogs opposite G and OG within DNA with high affinity; however, no enzymatic processing of these duplexes is observed. The specific nature of the interaction of MutY with an OG:FA duplex was demonstrated by MPE-Fe(II) hydroxyl radical footprinting experiments which showed a nine base pair region of protection by MutY surrounding the mispair. DMS footprinting experiments with an OG:A duplex revealed that a specific G residue located on the OG-containing strand was protected from DMS in the presence of MutY. In contrast, a G residue flanking the substrate analogs R, F or FA was observed to be hypersensitive to DMS in the presence of MutY. These results suggest a major conformational change in the DNA helix upon binding of MutY that exposes the substrate analog-containing strand. This finding is consistent with a nucleotide flipping mechanism for damage recognition by MutY. This work demonstrates that duplex substrates for MutY containing FA, R or F instead of A are excellent substrate mimics that may be used to provide insight into the recognition by MutY of damaged and mismatched base pairs within DNA.